2005
DOI: 10.1108/02686900510619665
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing auditor independence: Malaysian loan officers' perceptions

Abstract: Purpose -Auditor independence is fundamental to public confidence in financial reporting and the auditing profession. The study aims to provide further understanding of the factors influencing auditor independence from the perspective of commercial loan officers. Loan officers formed the sample as they are relatively sophisticated financial statement users who would understand the importance of audit report and the issues related to auditor independence. Design/methodology/approach -The study examines the perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 19 publications
1
24
1
1
Order By: Relevance
“…As summarized by Schneider et al (2006), prior studies reached mixed results but most generally the results indicate that NAS can negatively affect auditor independence perception. This view has been reinforced recently by spectacular corporate collapses and apparent audit failures associated with them.This is in line with the suggestions in prior literature advocating the use of the elements of independence (e.g., Abu Bakar et al, 2005;Chen et al, 2005;and Abu Bakar & Ahmad, 2009). …”
Section: Provision Of Non-audit Services (Nas)supporting
confidence: 80%
See 1 more Smart Citation
“…As summarized by Schneider et al (2006), prior studies reached mixed results but most generally the results indicate that NAS can negatively affect auditor independence perception. This view has been reinforced recently by spectacular corporate collapses and apparent audit failures associated with them.This is in line with the suggestions in prior literature advocating the use of the elements of independence (e.g., Abu Bakar et al, 2005;Chen et al, 2005;and Abu Bakar & Ahmad, 2009). …”
Section: Provision Of Non-audit Services (Nas)supporting
confidence: 80%
“…8, No. 17;2013 too consider tenure of audit firms as an element of independence external auditing (Act SOX, 2002;George, 2004;Abu Bakar et al, 2005;Jackson et al, 2008;Abu Bakar & Ahmad, 2009). …”
Section: Auditor Tenurementioning
confidence: 99%
“…Previous research suggests a positive association between audit firm size with auditor independence (Abu Bakar, Abdul Rahman, & Abdul Rashid, 2005;Abu Bakar & Ahmad, 2009;DeAngelo, 1981;Gul, 1989;Shockley, 1981). It has been found that larger audit firms has higher auditor's independence as they are often considered to be more able to resist pressures from management compared to small audit firms.…”
Section: Audit Firm Sizementioning
confidence: 96%
“…Regarding the perspectives of third parties such as bank loan officers, Abu Bakar, et al (2005) also reported a positive relationship between firm size and the level of auditor independence. Therefore, in our study on audit firm size and the likelihood that an auditor will support an audit exemption for SMEs, we hypothesis that:…”
Section: Audit Firm Size and The Auditor's Likelihood Of Supporting Amentioning
confidence: 97%
See 1 more Smart Citation